2004
DOI: 10.1093/jxb/erh149
|View full text |Cite
|
Sign up to set email alerts
|

Tomato fruit cuticular waxes and their effects on transpiration barrier properties: functional characterization of a mutant deficient in a very-long-chain fatty acid  -ketoacyl-CoA synthase

Abstract: Cuticular waxes play a pivotal role in limiting transpirational water loss across the plant surface. The correlation between the chemical composition of the cuticular waxes and their function as a transpiration barrier is still unclear. In the present study, intact tomato fruits (Lycopersicon esculentum) are used, due to their astomatous surface, as a novel integrative approach to investigate this composition- function relationship: wax amounts and compositions of tomato were manipulated before measuring unbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
287
0
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(322 citation statements)
references
References 37 publications
(40 reference statements)
23
287
0
8
Order By: Relevance
“…4B). The cutin layer is further covered by epicuticular waxes mostly made up of aliphatic compounds, which form a film at the surface of the fruit (Vogg et al, 2004;Buschhaus and Jetter, 2011). Because of these characteristics, wild-type fruit is moderately glossy.…”
Section: Tomato Ems Mutants For Studying Cuticle Composition and Propmentioning
confidence: 99%
See 1 more Smart Citation
“…4B). The cutin layer is further covered by epicuticular waxes mostly made up of aliphatic compounds, which form a film at the surface of the fruit (Vogg et al, 2004;Buschhaus and Jetter, 2011). Because of these characteristics, wild-type fruit is moderately glossy.…”
Section: Tomato Ems Mutants For Studying Cuticle Composition and Propmentioning
confidence: 99%
“…6). Likewise, the high proportion of cyclic triterpenoids found in the wax-rich glossy (P4E2) or dull (P6D6) mutants may modify the water loss properties of the fruit (Vogg et al, 2004;Buschhaus and Jetter, 2012).…”
Section: Tomato Ems Mutants For Studying Cuticle Composition and Propmentioning
confidence: 99%
“…15). The alkane abundance in S. pennellii and the higher ratio of alkanes to triterpenoids have previously been suggested as mechanisms for increasing resistance to water flux across the cuticle 9,10 . Additionally, the phenylpropanoid component of S. pennellii cutin was reduced to ~20% of that found in S. lycopersicum.…”
mentioning
confidence: 94%
“…Studies in cherry tomato (Solanum lycopersicum L.) demonstrated that the silencing of lecer6 elongase, involved in the extension of long-chain fatty acids, generated three to eight times more dehydration per unit surface area of fruit than the untransformed plant. These fatty acids are key components for the synthesis of aliphatic compounds like alkanes that are part of the cuticular wax (Vogg et al, 2004). The alkane's quantification for these tomatoes, showed a considerable decrease of the concentration of n-alkanes from 28 to 30 C (Leide et al, 2007).…”
Section: Biochemical Factors Involved In Cherry Fruit Crackingmentioning
confidence: 99%
“…Among the multiples genes found, there are wax biosynthesis transcriptional activators and genes involved in cell wall modification. Further evidence of the relationship between fruit cracking and properties and composition of the cuticle is provided by Vogg et al (2004) in tomato, where the mutation of the CER6 gene (β-ketoacyl-CoA synthase), leads to an alteration of the cuticular wax composition and increases water permeability. An interesting work about putative genes involved in the cuticle formation in sweet cherry was recently published by Alkio et al (2012).…”
Section: Genetics and Molecular Factors Involved In Fruit Crackingmentioning
confidence: 99%